2006
DOI: 10.1016/j.cell.2006.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Global, In Vivo, and Site-Specific Phosphorylation Dynamics in Signaling Networks

Abstract: Cell signaling mechanisms often transmit information via posttranslational protein modifications, most importantly reversible protein phosphorylation. Here we develop and apply a general mass spectrometric technology for identification and quantitation of phosphorylation sites as a function of stimulus, time, and subcellular location. We have detected 6,600 phosphorylation sites on 2,244 proteins and have determined their temporal dynamics after stimulating HeLa cells with epidermal growth factor (EGF) and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

178
3,418
13
19

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 3,236 publications
(3,651 citation statements)
references
References 61 publications
178
3,418
13
19
Order By: Relevance
“…The small response at the phosphoproteome level detected here is quite different from global quantitative phosphoproteomics studies that use cellular stimuli to directly regulate a particular kinase [72][73][74][75] or those studying cellular processes known to be greatly dependent on phosphorylation. 18,76 Much greater effects on phosphorylation throughout the entire signaling cascade are also observed, as expected.…”
Section: View Article Onlinementioning
confidence: 65%
“…The small response at the phosphoproteome level detected here is quite different from global quantitative phosphoproteomics studies that use cellular stimuli to directly regulate a particular kinase [72][73][74][75] or those studying cellular processes known to be greatly dependent on phosphorylation. 18,76 Much greater effects on phosphorylation throughout the entire signaling cascade are also observed, as expected.…”
Section: View Article Onlinementioning
confidence: 65%
“…This argues that binding of PP1 to p68 functions to regulate phosphorylation states of Pol d itself or of its neighbors within the replication machinery. The immediate target may be p68; phosphoproteomic studies have shown that p68 is phosphorylated at a minimum of six sites in vivo [Olsen et al, 2006]. These sites are in sequence contexts that indicate that they are sites for CK2 phosphorylation, and it has been shown that p68 is phosphorylated at multiple sites in vitro by CK2 [Gao et al, 2008;Lemmens et al, 2008].…”
Section: Regulation Of Pol D Activity By Protein Phosphorylationmentioning
confidence: 99%
“…Already, investigators have begun using phosphoproteomics to address real biological and clinical problems, such as unraveling important signaling networks and discovering how these networks malfunction in various types of cancer. [9][10][11][12][13] Despite the success of some initial biological and clinical applications of phosphoproteomics, researchers want to see more progress in the methods. " [Phosphoproteomics] should become routine," says Figeys, "the same way as doing protein identification from a gel band 15 years ago was very difficult, and now any decent lab in the world can do it."…”
Section: To Mainstream Research and Beyondmentioning
confidence: 99%